As Above, So Below: Art of the American Fraternal Society, 1850–1930, by Lynne Adele and Bruce Lee Webb, and The Badge of a Freemason: Masonic Aprons from the Scottish Rite Masonic Museum and Library, by Aimee E. Newell. (24th June 2018) - Dennis, Mark
Abstract : As Above, So Below: Art of the American Fraternal Society, 1850-1930, by Lynne Adele and Bruce Lee Webb, (Austin, TX: University of Texas Press, 2015), xxi + 266 pp., $60.00, Hbk, ISBN: 9780292759503. and The Badge of a Freemason: Masonic Aprons from the Scottish Rite Masonic Museum and Library, by Aimee Newell, (Lexington, MA: Scottish Rite Masonic Museum and Library, 2015), 247 pp., $39.95, Hbk, 9781889541020.